Application development in supplier-customer collaborations: success factors for firms in the process industries. (1st January 2012) - Lager, Thomas; Storm, Per
In the process industries, development with the external customer is not confined to the company's own product development and external customer technical services and support. A substantial part of the innovation activities of a firm lies in the area of helping its customers to use supplied products more effectively. This area is generally designated application development. Since a literature survey turned up few publications, a theoretical framework was developed and an exploratory survey was carried out of Swedish process industries. The importance to the firm of product and process development is never questioned. It is concluded that the area of application development should not be overlooked either, if recognised as relevant to a firm. The study population includes only firms which are based in Sweden, but since they have many customers on a global market it is argued that the research findings to some extent can be generalised to the larger world-wide population of interest.